Effect of 2-Methylimidazole Composition as Low-Temperature Application in Phenol-Formaldehyde, Glycidyl Ether Epoxy Coating - Rinush Fedrikdo Paltgor; Rini Riastuti; Rizal Tresna Ramdhani; Muhammad Yunus (BRIN Publishing (Penerbit BRIN), 2023)
The addition of materials to pile pipe at low temperatures is very challenging. Thereby, an optimum operating level is needed to produce a quality coating. Furthermore, 2-methylimidazole (2MI) was added into a phenol-formaldehyde, glycidyl ether polymer fusion bonded epoxy (FBE) coating at different concentrations of 1, 2, and 3 %wt. Thermal analysis was then carried out using differential scanning calorimetry (DSC), where the addition of 2MI decreased the curing temperature to 134.76°C due to the reduced activation energy. Potentiodynamic polarization showed the best corrosion rate of 0.00991 mm/year with a current density of 0.847μA/cm2 after adding 1 %wt 2MI. Electrochemical impedance spectroscopy (EIS) was carried out to determine the charge transfer resistance and maximum coating capacitor capacitance after adding 1 %wt 2MI, namely 9.9 kΩ and 8.45×10-5 F, respectively. The cathodic disbondment test (CD-Test) showed that the disbondment radius of the coating under the influence of the cathodic protection current was 4.32mm. Mechanical analysis by pull-off adhesion test showed a value of 7.28 MPa after the addition of 2MI 2 %wt but decreased to 6.63 MPa at 3 %wt. Therefore, the optimum addition is 1 %wt 2MI for low-temperature applications of 170 –175°C in piles with high coating performance and compliance with predetermined standards.